Kewajiban Notaris Membacakan Akta Autentik Bagi Penghadap Disabilitas Rungu - Adam Jose Sihombing; Gede Wahyu Adipramartha (Jurnal USM Law Review)
The purpose of this article is to analyze the regulations on the Notary's obligations in reading an authentic deed for a client or hearing person who is deaf, based on the regulations in force in Indonesia. In addition, this research was conducted to find out and examine the legal formulation regarding the obligation to read authentic documents that are relevant to the situation of clients or speakers who are deaf. Remembering Law No. 2 of 2014 concerning amendments to Law No. 30 of 2004 concerning the position of notaries and the legal formulation regarding the obligation to read authentic deeds relating to the situation of deaf disabled persons Normative legal research is carried out by examining various formal legal rules, such as laws, regulations, and literature containing theoretical concepts that are related to problems. The results of this study show that in the regulations regarding the obligation of notaries to read authentic deeds for deaf persons in the Notary Position Law in Indonesia, there is still a vacuum in norms and only regulates the reading of deeds intended for non-disabled persons or normal persons only. The Law on Notary Positions in Indonesia was amended to include provisions regarding sign language interpreters for deaf people, provided they have passed the sign language interpreter qualification exam held by the Professional Certification Institute established by a professional organization or university. This legal formulation answers the obligation to read authentic documents that are relevant to the situation of deaf people in the future.